(untitled) (Proceedings OPTIMAL, 2025)
The transition period of life that occurs during adolescence determines the self-concept that is formed. One of the factors that influences the formation of this self-concept is the involvement of father’s caregiving. The purpose of this study was to determine the relationship between father’s caregiving involvement and the formation of self-concept in adolescents at SMP 4 Pariaman. This type of research is quantitative with a cross-sectional approach. The independent variable is father’s caregiving involvement, while the dependent variable is self-concept. The sample taken was 53 students of SMPN 4 Pariaman with a random sampling technique. The research instrument used a questionnaire. Data analysis was carried out univariately to determine the frequency distribution and percentage of father’s caregiving involvement and self-concept. The bivariate test used the Chi-Square statistical test at a significance level of 5%. Univariate analysis showed that the majority of respondents, namely 29 students (54.7%) had fathers who were less involved in parenting and had a negative self-concept, namely 32 participants (60.38%). Bivariate analysis showed a significant relationship between father’s parenting involvement and the formation of adolescent self-concept at SMP 4 Pariaman (p value = 0.002 <α = 0.05) with OR = 8.5. It can be concluded that father’s parenting involvement is related to the formation of self-concept in adolescents at SMPN 4 Pariaman, West Sumatra Province